Manajemen Perencanaan Strategis Sistem Informasi Menggunakan Metode Tozer (Studi Kasus: SMK Bina Nusantara Ungaran) - Herry Sanoto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
Business competition in this fast-paced information age has become very tight. especially in the field of education. Thus the organization must have a business strategy that is very mature in order to face the competition. The application of information systems and technology has become one of the most influential business strategies for staying in competition. Bina Nusantara Ungaran Vocational School has implemented an information system and technology, but apparently it has not run optimally because some parts have not yet implemented an information system. In this study discusses how to plan an IS / IT strategy using the Tozer version method with supporting analysis such as Value Chain Porter's, Five Force Porter's, SWOT, Critical Success Factor, and McFarlan's Strategic Grid. Which produces a portfolio of SI / IT that is aligned with the vision and mission to support the business processes that are run and make Bina Nusantara Ungaran Vocational School excel in field of education.